# 2sin(x)sec(x)=sec(x)

## Simple and best practice solution for 2sin(x)sec(x)=sec(x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 2sin(x)sec(x)=sec(x) equation:

Simplifying
2sin(x) * sec(x) = sec(x)
Multiply ins * x
2insx * ces * x = sec(x)
Multiply insx * ces
2ceins2x * x = sec(x)
Multiply ceins2x * x
2ceins2x2 = sec(x)
Multiply ces * x
2ceins2x2 = cesx
Solving
2ceins2x2 = cesx
Solving for variable 'c'.
Move all terms containing c to the left, all other terms to the right.
Add '-1cesx' to each side of the equation.
2ceins2x2 + -1cesx = cesx + -1cesx
Combine like terms: cesx + -1cesx = 0
2ceins2x2 + -1cesx = 0
Factor out the Greatest Common Factor (GCF), 'cesx'.
cesx(2insx + -1) = 0
Subproblem 1Set the factor 'cesx' equal to zero and attempt to solve:
Simplifying
cesx = 0
Solving
cesx = 0
Move all terms containing c to the left, all other terms to the right.
Simplifying
cesx = 0
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
Subproblem 2Set the factor '(2insx + -1)' equal to zero and attempt to solve:
Simplifying
2insx + -1 = 0
Reorder the terms:
-1 + 2insx = 0
Solving
-1 + 2insx = 0
Move all terms containing c to the left, all other terms to the right.
Add '1' to each side of the equation.
-1 + 1 + 2insx = 0 + 1
Combine like terms: -1 + 1 = 0
0 + 2insx = 0 + 1
2insx = 0 + 1
Combine like terms: 0 + 1 = 1
2insx = 1
Add '-2insx' to each side of the equation.
2insx + -2insx = 1 + -2insx
Combine like terms: 2insx + -2insx = 0
0 = 1 + -2insx
Simplifying
0 = 1 + -2insx
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
The solution to this equation could not be determined.`